Fatigue in Context of Gender and Concrete Structure for Sustainable Development-A Comparable Thought - Yadav, Indra Narayan; Thapa, Kamal Bahadur (Journal of Innovations in Engineering Education, 2020)
Application of smaller stress lesser than ultimate capacity at the repeated number of cycles to the concrete and Gender "sudden death" i.e. hearth attack in terms of damage is occurred called "Fatigue". Unequal Pay, Interview questions, Diminished responsibilities, Restrooms, Conversations, Glass Ceilings, Political bias, Terminations, Outdated views, Sexual Harassments, the main causes of gender fatigue in terms of compassion fatigue were compared to the general fatigue in concrete are well described in this paper from the stone age to till age, the dominant character as diligent shaker in the second world war was created the female gender fatigue such as the nuclei-propagation of microdefects, microvoids and fractal of rendered concrete in conjunction with more compliant are well discussed in comparative way. The product of service life along performance with environmental impact refers the degree of sustainability is well discussed by comparing the fatigue in terms of gender and concrete structure in different manners and hypothesis seems the much correlated results are validated by Microdefects, microvoids in concrete as Dalit, Dorry, Dahej, Daridra, Dar, Danger, Dominant, Dom, Dard, Dakait, Damai, Disadvantages Groups, Disable Group, Deaf, Disability etc. the majority of Nepali words and indicator of UN SDG's Viruses.